An Assessment of the Optimal Techniques for Sampling Shallow Water Reef Fishes - Jessop, Sarah Ann (Curtin University, 2022)
I compared four methods of sampling fish assemblages, including underwater visual census, diver operated stereo-video, baited remote underwater stereo-video and a remote operated vehicle with an attached stereo-video system. Comparisons focused on the assemblage composition sampled, number of individuals and species sampled, length-based metrics and fish behaviour. I concluded that a combination of baited remote underwater stereo-video and a remote operated vehicle with attached stereo-video system is the optimal approach to sampling a representative suite of fishes.